2008
DOI: 10.1103/physrevb.78.104524
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Born impurity scattering near the surface ofd-wave superconductors and influence of external magnetic field

Abstract: We study the influence of self-consistent Born impurity scattering on the zero-energy Andreev bound states near the surface of a d-wave superconductor with and without an externally applied magnetic field. Without an external magnetic field we show that the effect of Born impurity scattering is stronger at the surface than in the bulk. In the presence of an external magnetic field the splitting of the zero-energy Andreev bound states is shown to have a nonmonotonous temperature dependence. Born impurity scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These states split in the presence of a screening current [13][14][15] and they carry an anomalous counter-flowing paramagnetic surface current [13,16]. In previous work we have shown that the anomalous surface current leads to a strong modification of linear response properties [17,18]. Here, we study their influence on the nonlinear Meissner effect.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These states split in the presence of a screening current [13][14][15] and they carry an anomalous counter-flowing paramagnetic surface current [13,16]. In previous work we have shown that the anomalous surface current leads to a strong modification of linear response properties [17,18]. Here, we study their influence on the nonlinear Meissner effect.…”
mentioning
confidence: 94%
“…The full set of equations and a description of the numerical solution procedure based on the Riccati technique [22] can be found in Ref. [19]. We consider a homogeneous superconducting halfspace in the region x !…”
mentioning
confidence: 99%
“…Artificially introduced internal surfaces can be very rough in the experiment, whereas surfaces are specular in the theory. Actually, several theories have pointed out that the surface roughness affects properties of the surface Andreev bound states of a high-T c superconductor [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we have studied the transport property of the d + ip-wave junction in the ballistic limit by calculating the tunneling conductance. The induced p-wave pair, however, is more fragile against impurity scatterings than s-wave pairs 27,[62][63][64][65] . Thus, in the presence of disorder, the differential conductance of the d + ip-and d + is-wave junctions may be different.…”
Section: Discussionmentioning
confidence: 99%